Split-parallel through-the-road hybrid electric vehicle: Operation, power flow and control modes - Zulkifli, S.A. (Institute of Electrical and Electronics Engineers Inc., 2015)
A split-parallel hybrid electric vehicle (HEV) is a particular sub-type of the HEV in which the internal combustion engine (ICE) and electric motor provide propulsion power to different axles. Due to the coupling of power through the vehicle itself, its wheels and the road on which it moves - rather than through some mechanical device - the vehicle is referred to as a 'through-the-road' (TTR) hybrid. A variant of the TTR hybrid has the motors in the hub of the otherwise non-driven wheels, called in-wheel motors (IWM). This configuration enables an existing vehicle to be converted into a hybrid vehicle with minimal modification. The present work identifies specific operating modes and power flow of the TTR-IWM hybrid, specifically a retrofit-conversion hybrid, in comparison to the ordinary parallel hybrid vehicle. It discusses control architecture, control objectives and system parameters, along with specific control issues of the retrofit TTR-IWM hybrid vehicle. Â© 2015 IEEE.